#1**+10 **

3x - y = 23 (1)

2x + 3y = 8 (2)

Multiply all terms in (1) by 3

9x - 3y = 69 (3)

Now there are the same number of y's in equation (3) as in equation (2), so add equation (2) to equation (3) term by term:

11 x = 77

so x = 11

Plug this back into equation (1)

3*11 - y = 23 or 33 - y = 23

Subtract 23 from both sides

10 - y = 0

Add y to both sides

10 = y (or y = 10)

.

Alan
Apr 2, 2015

#1**+10 **

Best Answer

3x - y = 23 (1)

2x + 3y = 8 (2)

Multiply all terms in (1) by 3

9x - 3y = 69 (3)

Now there are the same number of y's in equation (3) as in equation (2), so add equation (2) to equation (3) term by term:

11 x = 77

so x = 11

Plug this back into equation (1)

3*11 - y = 23 or 33 - y = 23

Subtract 23 from both sides

10 - y = 0

Add y to both sides

10 = y (or y = 10)

.

Alan
Apr 2, 2015